TNF-Like Weak Inducer of Apoptosis Aggravates Left Ventricular Dysfunction after Myocardial Infarction in Mice - Kai-Uwe Jarr; Sabine Eschricht; Linda C. Burkly; Michael Preusch; Hugo A. Katus; Norbert Frey; Emmanuel Chorianopoulos (Mediators of Inflammation)
Background. TNF-like weak inducer of apoptosis (TWEAK) has recently been shown to be potentially involved in adverse cardiac remodeling. However, neither the exact role of TWEAK itself nor of its receptor Fn14 in this setting is known. Aim of the Study. To analyze the effects of sTWEAK on myocardial function and gene expression in response to experimental myocardial infarction in mice. Results. TWEAK directly suppressed the expression of PGC-1α and genes of oxidative phosphorylation (OXPHOS) in cardiomyocytes. Systemic sTWEAK application after MI resulted in reduced left ventricular function and increased mortality without changes in interstitial fibrosis or infarct size. Molecular analysis revealed decreased phosphorylation of PI3K/Akt and ERK1/2 pathways associated with reduced expression of PGC-1α and PPARα. Likewise, expression of OXPHOS genes such as atp5O, cycs, cox5b, and ndufb5 was also reduced. Fn14 -/- mice showed significantly improved left ventricular function and PGC-1α levels after MI compared to their respective WT littermates (Fn14 +/+). Finally, inhibition of intrinsic TWEAK with anti-TWEAK antibodies resulted in improved left ventricular function and survival. Conclusions. TWEAK exerted maladaptive effects in mice after myocardial infarction most likely via direct effects on cardiomyocytes. Analysis of the potential mechanisms revealed that TWEAK reduced metabolic adaptations to increased cardiac workload by inhibition of PGC-1α.